2020
DOI: 10.1155/2020/6982438
|View full text |Cite
|
Sign up to set email alerts
|

The Supernatant of Tonsil-Derived Mesenchymal Stem Cell Has Antiallergic Effects in Allergic Rhinitis Mouse Model

Abstract: Background and Purpose. Recently, tonsil-derived mesenchymal stem cells (T-MSCs) have attracted great attention in various medical fields due to easier harvest of T-MSCs and more immunomodulatory effects than adipose-derived MSCs. However, there was still little evidence of the effect of conditioned media from T-MSCs (T-MSCs-CM) on allergic rhinitis (AR). Therefore, we investigated the impact of T-MSCs-CM on an AR mouse model. Methods. We isolated T-MSCs from human palatine tonsil and evaluated the ingredients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…De Corgnol et al used olfactory ensheathing cells, in rats with vagus nerve section, and reported the reinnervation in the vocal folds [177]. Transplantation of tonsil-derived stem cells in mice allergic rhinitis model showed significantly decreased allergic symptoms, a reduced infiltration of eosinophils and neutrophils in the nasal mucosa and a significantly declined IL-4 mRNA expression that can demonstrate the immunomodulatory effect of tonsil-derived stem cells via inhibition of T cell activation, mitogen-activated protein (MAP) kinase, p65, and NFAT1 [178]. The intravenous injection of tonsil-derived stem cells, in a model of allergic rhinitis in mice, induced by ovalbumin, showed a significantly reduced allergic symptoms, a decrease in eosinophil infiltration, a decline in total serum and immunoglobulin E (IgE), a reduction in the nasal and systemic Th2 cytokine profile, and finally, an inhibition in allergic inflammation [179].…”
Section: In Vivo Studies In Rhinologymentioning
confidence: 95%
“…De Corgnol et al used olfactory ensheathing cells, in rats with vagus nerve section, and reported the reinnervation in the vocal folds [177]. Transplantation of tonsil-derived stem cells in mice allergic rhinitis model showed significantly decreased allergic symptoms, a reduced infiltration of eosinophils and neutrophils in the nasal mucosa and a significantly declined IL-4 mRNA expression that can demonstrate the immunomodulatory effect of tonsil-derived stem cells via inhibition of T cell activation, mitogen-activated protein (MAP) kinase, p65, and NFAT1 [178]. The intravenous injection of tonsil-derived stem cells, in a model of allergic rhinitis in mice, induced by ovalbumin, showed a significantly reduced allergic symptoms, a decrease in eosinophil infiltration, a decline in total serum and immunoglobulin E (IgE), a reduction in the nasal and systemic Th2 cytokine profile, and finally, an inhibition in allergic inflammation [179].…”
Section: In Vivo Studies In Rhinologymentioning
confidence: 95%
“…adipose-derived MSCs [11][12][13][14]. Some studies showed that exogenously administered T-MSCs migrate to damaged tissue sites and participate in tissue repair by immune regulatory functions in a mouse model of liver injury [15,16].…”
Section: Characterization Of Tonsil Derived Mesenchymal Stem Cellmentioning
confidence: 99%
“…Tonsil-derived mesenchymal stem cells (T-MSCs) have recently been introduced and have been getting a great deal of attention in various medical fields due to them being easier to harvest than BM-MSCs. They also have more immunomodulatory effects than adipose-derived MSCs [11][12][13][14]. Some studies showed that exogenously administered T-MSCs migrate to damaged tissue sites and participate in tissue repair by immune regulatory functions in a mouse model of liver injury [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…47 Several previous studies have also shown that T-MSCs and conditioned media released by T-MSCs (T-MSCs-CM) have an anti-allergic effect. 8,9…”
Section: Introductionmentioning
confidence: 99%